Structural deformation mechanism of the hat-stiffened plate used in marine structures under impact load. (15th December 2022) - Wang, Zeping; Liu, Kun; Yu, Tongqiang; Zong, Shuai; Wang, Xiufei
Abstract: As the basic structure of the bottom or side of the ship structure or marine structure, the stiffened plate plays the main energy absorption role in the collision accident. In the design of ship crashworthiness structure, the design improvement of the stiffened plate structure can improve the crashworthiness of the ship. In this paper, the damage deformation mode of the hat-stiffened plate is determined by designing and conducting the falling weight impact test, and the analytical formulas for the instantaneous resistance of the structure is derived based on the theory of plastic mechanics. The accuracy of the analytical calculation method is verified by comparing with the test results, and the analytical calculation formula for calculating the instantaneous structural resistance of the hat-stiffened plate proposed in this paper can quickly evaluate the response of the structure under accident loads, which is of guiding significance for the structural design of marine structures. Highlights: The structural deformation mechanism of the hat-stiffened plate used in marine structures under impact load is researched. Based on the results from the test, the deformation characteristics of the hat-stiffened plate are obtained. The analytical calculation formula of the instantaneous structural resistance of the hat-stiffened plate is deduced. The proposed theoretical deformation model can reflect the main deformation process. The proposed analytical model is of important engineering application value for the structural crashworthiness evaluation.